(untitled) (Libellarium: journal for research in the field of information and related sciences, 2024)
Objective. The aim of this paper is to explore the development and changes in the publishing policy of the women’s magazine Ženski list, whose chief editor was Marija Jurić Zagorka. The magazine was published during the interwar period and significantly influenced the residents of the Kingdom of Yugoslavia and emigrants abroad with its content. Approach/Methodology. The analysis of the magazine was conducted based on the most visually striking and/or important issues from each year of publication, totaling 14 issues. The analysis included the number of pages, quantity of illustrations and advertisements, citation of responsibility data, and graphic and thematic changes in the magazine design. Sources from the Stare novine portal and the Center for Women’s Studies were used. Results. The paper provides a brief historical overview of women’s magazines worldwide, in Europe, and in the Kingdom of SHS/Yugoslavia. Furthermore, Marija Jurić Zagorka is highlighted as the journalist, and editor, followed by an analysis of the magazine issues. The uniqueness of this magazine lies in achieving high circulation and reaching readers from all social circles. Despite financial difficulties due to the non-receipt of subscriptions and economic crises, the magazine, in its 14 years of publication, kept up with innovations in the layout of visual and textual contributions. A significant increase in illustrations and advertisements is noted, indicating the magazine’s close connection to its social environment, especially businesses and shops in Zagreb. There is also an observed increase in attributing authors to texts and photos or indicating the source from which the content was taken, demonstrating the editorial understanding of the concept of intelectual property. Originality/Value. This paper provides an overview of publishing and editorial practices. In addition to technical characteristics, the paper offers a partial insight into the magazine’s content, placing it in the context of publishing for women, by women, in the 1920s and 1930s.